2011
DOI: 10.1186/1471-2091-12-51
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an exopolygalacturonase from Fusarium oxysporum f.sp. cubense race 1 and race 4

Abstract: BackgroundFusarium wilt is an economically devastating disease that affects banana production. Although Cavendish banana cultivars are resistant to Fusarium oxysporum f.sp. cubense race 1 (FOC1) and maitain banana production after Gros Michel was destructed by race 1, a new race race 4 (FOC4) was found to infect Cavendish.ResultsAn exopolygalacturonase (PGC2) was isolated and purified from the supernatant of the plant pathogen Fusarium oxysporum f.sp. cubense race 4 (FOC4). PGC2 had an apparent Mr of 63 kDa by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…The sample application on SDS-PAGE showing one single protein band indicated that PGC3 was purified to homogeneity and had a molecular weight of 45 kDa according to the markers ( Figure 1 ), which was different from PGC2 (63 kDa) purified previously [ 14 ]. It is obvious that there is more than one PG in FOC4 like other pathogenic fungus.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The sample application on SDS-PAGE showing one single protein band indicated that PGC3 was purified to homogeneity and had a molecular weight of 45 kDa according to the markers ( Figure 1 ), which was different from PGC2 (63 kDa) purified previously [ 14 ]. It is obvious that there is more than one PG in FOC4 like other pathogenic fungus.…”
Section: Resultsmentioning
confidence: 71%
“…Both purified recombinant PGC3 from both FOC1 and FOC4 exhibited optimum activity at pH 4.5 ( Figure 4 a), and the highest activity at 50 °C ( Figure 4 b). Similarly, the optimum pH and temperature of PGC2 from FOC4 were 5 and 50 °C, respectively [ 14 ], and the pH value and temperature optima for the PG activity from PG2 of Fusarium oxysporum f. sp. lycopersici (FOL) were 5 and 55 °C [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Protein banding pattern of fungal isolates allowed identification of multiple protein bands as shown in Figure 1. The molecular weights of the P. aphanidermatum proteins ranged from approximately 15 to 95 kDa (Anusuya & Sathiyabama, 2014;Ray et al, 2016) and of F. oxysporum proteins from 14 to 116 kDa (Bhuvanendra et al, 2010;Dong & Wang, 2011). Analysis of fungal proteins showed several specific protein bands which were absent in healthy ginger rhizomes.…”
Section: Sds-page Analysismentioning
confidence: 99%
“…The virulence proteins that have been characterized from F1 and F4 are involved in signal transduction, transcription, defense system, and colonization [2] . They include G-proteins [7] , mitogen-activated protein kinase [22] , signal transcription factor [13] , [23] , glucosidase [23] , polygalacturonase [24] , and mitochondrial carrier protein [25] . Proteomics studies in Fusarium graminearum [26] , [27] and F. oxysporum [28] , [29] identified 174 cell wall proteins and 19 proteins carrying predicted signal peptides in F. oxysporum , including glucose-regulated protein, acid phosphatase, cell wall glucanosyltransferase, glucanase, secreted aspartic protease, and vacuolar protease [28] .…”
Section: Discussionmentioning
confidence: 99%